Expert System of Tuberculosis Diagnosis Using Web-Based Certainty Factor (CF) Method: Expert System of Tuberculosis Diagnosis Using Web-Based Certainty Factor (CF) Method - Wilsen Wilsen; Moh. Iwan Wahyuddin; Ratih Titi Komalasari (Institute of Computer Science (IOCS), 2020)
Tuberculosis is an infectious disease caused by the bacteria mycobacterium tuberculosis. In 2017 Indonesia entered into the third largest number of TB cases in the world. Lack of public knowledge of the dangers of tuberculosis makes this disease is growing rapidly. This is the main reason why it is necessary to create a system that can diagnose the early symptoms of the disease so that it can assist in tackling tuberculosis early. An expert system is one of the techniques in the diagnosis of disease. This research aims to develop applications early diagnosis of tuberculosis disease system is expected to facilitate the public in the early diagnosis of tuberculosis. The system uses the calculation of symptoms / complaints using CF (certainty factor). Results of testing performed by the system and test method validation black box shows that each feature can work with both the application and the content therein can be trusted. In addition, this system is quite powerful in handling more users are accessing the system simultaneously.